VIDEOLAPAROSCOPIC CHOLECYSTECTOMY IN PATIENTS SUBJECTED TO OPERATIONS ON ORGANS OF THE ABDOMINAL CAVITY IN THE EARLIER PERIOD - Khvorostov, E.D.; Tsivenko, A.I.; Bychkov, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
For the period from 1994 year 1486 patients with chronic and acute calculosus cholecystitis aged from 18 to 78 years old were operated in the hospital. 312 patients of them were subjected to operations on organs of the abdominal cavity in the earlier period. Peculiarities of the operative treatment in this group of patients are elucidated in the article, particularly carrying out of the videolaparoscopic cholecystectomy. Au thors based possibility and expedientness of fulfilment of videolaparoscopic cholecystectomy in patients subjected to operations on organs of the abdominal cavity earlier.